Factorization for bounded analytic functions in the unit disk and an application to prime ideals - Mortini, Raymond (MATHEMATICA SCANDINAVICA, 2006)
We prove several factorization theorems for bounded analytic functions in the open unit disk and present a very simple new proof of two conjectures of Frank Forelli and the author on the structure of finitely generated, respectively countably generated prime ideals in $H^{∞}$.